Political Theory of Nation-Building:Case of the Failed State of Afganistan in 2021: Part 1 - Betz, Frederick (Advances in Social Sciences Research Journal, 2022)
Why is it important to get social science methodology correct? It is important because invalid social science theory may be used to formulate governmental policies which are wrong – incompetent and even harmful. A modern (and tragic) example of invalid social theory with bad policy is the case of America’s 20-year effort in ‘nation-building’ by occupying Afghanistan. In 2021, the policy ended dramatically with the rapid fall of the Afghan government and the triumph again of the Taliban. Afghanistan was a failed state, after a history of a series of invasions. In this research, we analyze the theory of nation-building, which can be verified by this historical event. The cross-disciplinary social science theory of nation-building is that it should be a two-directional process: with both up-and-down perspectives on building a nation from a state. This theory was analyzed empirically in a previous paper by the author, to explain the failure of nation-building in Lebanon. (Betz, 2020) Here we analyze use the theory of nation-building to explain a historical case of policy failure in Afghanistan. This theory of two strategic directions of nation-building, top-down and bottom-up, are validated in the histories of two different societies. Social science theory verified in two or more societal histories is likely to be generalizable to any modern society.